Patient Experiences of Service Quality and its Impact on Satisfaction at B&B Hospital - Alam Miya, Makshud; Prasad Sharma, Sushil (Nepalese Journal of Insurance and Social Security, 2024)
Purpose: The research paper attempted to provide the consensus regarding the influence of perceptual service quality on customer satisfaction at B&B hospital in Lalitpur district. Design/methodology/approach: Impact were assessed in 2024 in Lalitput, Nepal by employing 186 samples with the help of convenience sampling method. Sample were selected from existing patients from the B&B hospital. Five-point Likert scale question were asked and the validity and reliability of the questionnaire were confirmed. Findings: Measure of central tendency and dispersions, correlation and regression analysis were used through SPSS 25. Study found that the patients perceived better service quality in case of outpatient department of the hospitals, and services of the hospitals were found better based on the patient experience. Conclusion: The study reveals that B&B Hospital meets patient expectations through high service quality, with physician consultation, perceived costs, and physical environment influencing satisfaction, highlighting the need for strategic enhancements. Implications: The study implies that hospitals can boost patient satisfaction and attract more patients by investing in staff training, enhancing communication, creating a comfortable environment, and addressing service costs, thus differentiating themselves through targeted service improvements. JEL Classification: I11, I13, I18